Biodiesel Production from Nyamplung (Calophyllum inophyllum) Oil using Ionic Liquid as A Catalyst and Microwave Heating System - Prima Astuti Handayani; Abdullah Abdullah; Hadiyanto Hadiyanto (Bulletin of Chemical Reaction Engineering & Catalysis, 2017)
Nyamplung (Calophyllum inophyllum) is a typical Indonesian plant. Its seed contains abundant inedible oil, and therefore it is potential for biodiesel feedstock. The current issues of biodiesel are longer  reaction time of oil to biodiesel through transesterification reaction and lower biodiesel yield due to ineffective use of a homogenous catalyst. This work was aimed to use an ionic liquid as a catalyst and equipped with microwave heating as the heating system in order to increase the biodiesel yield and accelerate the process. Effects of the catalyst concentration and power of microwave irradiation to the biodiesel yield were studied. The ionic liquid of 1-butyl-3-methylimidazolium hydrogen sulfate (BMIMHSO4) was used as a catalyst. The results showed that the highest biodiesel yield was achieved of 92.81% which was catalyzed by IL0.5NaOH0.5 (0.5 wt.% (BMIMHSO4) + 0.5 wt.% NaOH) with a methanol-to-oil molar ratio of 9, a reaction time of 6 minutes, and the microwave temperature was 60 °C.